Cochrane Database of Systematic Reviews 2007
DOI: 10.1002/14651858.cd006420
|View full text |Cite
|
Sign up to set email alerts
|

Isolation as a strategy for controlling the transmission of hepatitis C virus (HCV) infection in haemodialysis units

Abstract: The risk in the intervention group (and its 95% conf idence interval) is based on the assum ed risk in the com parison group and the relative effect of the intervention (and its 95% CI).CI: Conf idence interval; RR: Risk ratio GRADE Working Group grades of evidence High quality: We are very conf ident that the true ef f ect lies close to that of the estim ate of the ef f ect M oderate quality: We are m oderately conf ident in the ef f ect estim ate: The true ef f ect is likely to be close to the estim ate of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 52 publications
1
6
0
Order By: Relevance
“…Also studies done in Saudi Arabia and Spain supported our finding and added that, strict isolation is mandatory in HD units [35,36]. But in another study done in Peru, they did not found differences in terms of the number of participants developing HCV infection when comparing the use of dedicated HD machines for HCV infected patients with the use of nondedicated machines [11].…”
Section: Discussionsupporting
confidence: 73%
“…Also studies done in Saudi Arabia and Spain supported our finding and added that, strict isolation is mandatory in HD units [35,36]. But in another study done in Peru, they did not found differences in terms of the number of participants developing HCV infection when comparing the use of dedicated HD machines for HCV infected patients with the use of nondedicated machines [11].…”
Section: Discussionsupporting
confidence: 73%
“…19,41 Other protocols, such as the United Kingdom Renal Association and European Renal Best Practice, do not recommend isolation as a preventive measure. 42,43 A recent Cochrane systematic review 44 showed that the quality of evidence for or against isolation is very poor. Of the 123 papers evaluated, only one Randomized Controlled Trial (RCT) was found, 45 and even in that study the level of evidence was considered low.…”
Section: Isolationmentioning
confidence: 99%
“…In most of them, the study design is based on the intervention of isolation compared to its own historical controls, which creates a bias about the real reason for reducing incidence if it is directly related to the strategy or to the indirect effect of increased surveillance. 19,44 The strategy of optimizing and strengthening universal care seems to be quite effective in controlling HCV infection, so many specialists suggest it as a primary measure, and the isolation is necessary when these practices are flawed. Observational studies show that isolation did not protect against HCV infection, and in the latter CDC guidelines such an attitude is not recommended.…”
Section: Isolationmentioning
confidence: 99%
“…Benefits and arms of isolation for what concerns in-center HCV diffusion remain unclear as robust RCTs are missing [134]. Isolation strategies were those including a number of policies with various grades of intensity, such as using dedicated dialysis machines, staff, room or dialysis shift.…”
Section: Rationalementioning
confidence: 99%